Papermaking method to improve freeness

By adding a cationic or amphoteric water-soluble polymer and an organic acid to papermaking raw materials, the method addresses retention and drainage issues, improving freeness and water extraction to enhance productivity and quality.

JP2025009112APending Publication Date: 2025-01-20HYMO CORPORATION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023111880
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-07
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Existing papermaking processes face challenges in maintaining retention rates of raw materials while improving drainage and water extraction properties, leading to reduced productivity and paper quality.

Method used

The addition of a cationic or amphoteric water-soluble polymer with specific composition to papermaking raw materials, followed by an organic acid, enhances retention and drainage performance without reducing yield rates.

Benefits of technology

This method improves freeness and water extraction performance, thereby increasing productivity and paper quality by maintaining or enhancing retention effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025009112000001
    Figure 2025009112000001
  • Figure 2025009112000002
    Figure 2025009112000002
  • Figure 2025009112000003
    Figure 2025009112000003
Patent Text Reader

Abstract

To provide a papermaking method of papermaking raw paper using a yield freeness improvement system in a papermaking process, which is to improve freeness and water-squeezing property without causing decrease of yield of the papermaking raw paper with a wire even when increasing an addition ratio.SOLUTION: By applying a papermaking method where a cationic or an amphoteric water-soluble polymer having a specified composition is added to papermaking raw paper before paper-making, followed by adding an organic acid, freeness and water-squeezing property can be improved without lowering yields. Preferably, the organic acid has the same or different kinds of groups selected from a carboxy group, a sulfonic acid group, and a phenolic hydroxyl group.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a papermaking method that uses a retention and drainage improver in the papermaking process, and more particularly, to a papermaking method that improves retention and drainage of papermaking raw materials on a wire by a retention and drainage improvement system that uses a retention and drainage improver in the papermaking process. [Background technology]

[0002] In the papermaking process for coating base paper, PPC paper, fine paper, paperboard, newsprint, etc., retention aids are used to improve the retention rate on the wire of raw pulp, fine fibers, fillers, papermaking chemicals, etc., and drainage aids (or retention and drainage improvers) that emphasize the function of improving drainage as well as retention are used. Generally, polyacrylamide (PAM) polymers are widely used as these agents, but due to the diversification of papermaking conditions in recent years, the effective retention and drainage improvers and yield and drainage improvement systems vary. As a system for improving retention and drainage using two or more liquids, various systems have been proposed that take into consideration the ion balance, mainly using PAM-based polymers, according to the papermaking conditions and the properties of the papermaking raw materials. For example, there is a prescription in which a cationic or amphoteric PAM is added, followed by an anionic PAM (Patent Document 1), and a prescription in which a cationic synthetic polymer with a high intrinsic viscosity is added, followed by a branched anionic water-soluble polymer with an intrinsic viscosity exceeding 3 dl / g and a tan δ at 0.005 Hz of 0.5 or more (Patent Document 2). However, although these prescriptions can improve the retention rate of the papermaking raw materials, excessive water is taken up into the flocs formed by the anionic PAM added to the second liquid, which often results in reduced drainage and water squeezing, resulting in reduced productivity. Therefore, various prescriptions for improving retention and drainage that do not reduce drainage and water squeezing have been proposed. For example, there is a prescription in which a cationic polymer is added, followed by the addition of an anionic inorganic substance, bentonite (Patent Document 3), and a prescription in which an acrylamide-based polymer having a cationic group and colloidal silicic acid are added (Patent Document 4). However, although these prescriptions tend to improve drainage and water squeezing, the retention effect is often insufficient. Therefore, there is a demand for a system for improving retention and drainage that can maintain the retention effect of the papermaking raw material in the wire part and improve drainage and water squeezing, especially in order to increase production efficiency.

[0003] [Patent Document 1] JP 2001-254290 A [Patent Document 2] Special Publication No. 2002-509587 [Patent Document 3] Japanese Unexamined Patent Publication No. 62-191598 [Patent Document 4] Japanese Patent Publication No. 15391 / 1983 Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention relates to a method for making paper from raw paper using a retention / drainage improver in the papermaking process, and an object of the present invention is to provide a papermaking method that can improve drainage and squeezing without reducing the retention rate of the raw paper on the wire. [Means for solving the problem]

[0005] As a result of intensive research to solve the above problems, it was discovered that by adding a cationic or amphoteric water-soluble polymer having a specific composition to the papermaking raw material before papermaking, and then adding an organic acid, the retention effect of the papermaking raw material on the wire can be maintained or improved, and improved drainage and water squeezing can be achieved. Effect of the Invention

[0006] By adding the cationic or amphoteric water-soluble polymer of the present invention to the papermaking raw material before papermaking, and then adding an organic acid, it is possible to improve drainage and water squeezing properties without reducing the yield even when the addition rate is increased, thereby achieving improved productivity and paper quality. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] The cationic or amphoteric water-soluble polymer in the present invention is produced by polymerizing an aqueous monomer mixture solution containing 5 to 100 mol % of a cationic monomer represented by the following general formula (1), 0 to 30 mol % of an anionic monomer represented by the following general formula (2), and 0 to 95 mol % of a nonionic monomer. The content of the cationic monomer represented by general formula (1) is preferably 5 to 50 mol %, more preferably 5 to 30 mol %. This is because when the cationic monomer is in this range, a polymer having a high molecular weight is easily obtained. JPEG2025009112000001.jpg2460 General formula (1) R1 represents hydrogen or a methyl group, R2 and R3 represent an alkyl group or an alkoxy group having 1 to 3 carbon atoms, R4 represents an alkyl group or an alkoxy group having 1 to 3 carbon atoms, an alkyl group or an aryl group having 7 to 20 carbon atoms, A represents oxygen or NH, B represents an alkylene group having 2 to 4 carbon atoms, X1 - represents an anion. JPEG2025009112000002.jpg2671 General formula (2) R5 is hydrogen, methyl or carboxymethyl, and Q is SO3 - , C6H4SO3 - , CONHC(CH3)2CH2SO3 - , C6H4COO - Or COO - R6 represents hydrogen or COOY2, and Y1 or Y2 represents hydrogen or a cation.

[0008] Examples of cationic monomers represented by general formula (1) include the following. That is, quaternized products of dimethylaminoethyl (meth)acrylate, dimethylaminopropyl (meth)acrylamide, etc. with methyl chloride or benzyl chloride. Examples include (meth)acryloyloxyethyl trimethylammonium chloride, (meth)acryloyloxy-2-hydroxypropyl trimethylammonium chloride, (meth)acryloylaminopropyl trimethylammonium chloride, (meth)acryloyloxyethyl dimethylbenzylammonium chloride, (meth)acryloyloxy-2-hydroxypropyl dimethylbenzylammonium chloride, and (meth)acryloylaminopropyl dimethylbenzylammonium chloride. Two or more of these can also be combined.

[0009] Examples of the anionic monomer represented by the general formula (2) include vinylsulfonic acid, vinylbenzenesulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid, methacrylic acid, acrylic acid, itaconic acid, maleic acid, fumaric acid, p-carboxystyrene acid, and salts thereof. Two or more of these may be used in combination.

[0010] Examples of the nonionic monomer used in the present invention include (meth)acrylamide, N,N'-dimethylacrylamide, acrylonitrile, 2-hydroxyethyl (meth)acrylate, diacetone acrylamide, N-vinylpyrrolidone, N-vinylformamide, N-vinylacetamide, acryloylmorpholine, etc. Two or more of these may be used in combination.

[0011] The product form of the cationic or amphoteric water-soluble polymer in the present invention is not particularly limited, and can be produced by a known method. It can be produced by copolymerizing a monomer mixture containing a cationic monomer and / or an anionic monomer and a nonionic monomer. After preparing an aqueous solution of these monomers, the polymerization is carried out by, for example, aqueous solution polymerization, water-in-oil emulsion polymerization, water-in-oil dispersion polymerization, dispersion polymerization in salt water, etc., and then any product form such as an aqueous solution, water-in-oil emulsion, dispersion in salt water, or powder can be used. For cationic or amphoteric water-soluble polymers, among these polymerization methods, water-in-oil emulsion polymerization or dispersion polymerization in salt water is preferred, which is easy to produce a polymer with a high molecular weight.

[0012] The water-in-oil emulsion can be appropriately produced according to the method described in JP-A-55-137147, JP-A-59-130397, JP-A-10-140496, JP-A-2011-99076, etc. That is, a monomer mixture containing a cationic monomer and a nonionic monomer is mixed with water, an oily substance consisting of a hydrocarbon immiscible with water, and at least one surfactant having an effective amount and HLB for forming a water-in-oil emulsion, and the mixture is stirred vigorously to form a water-in-oil emulsion, followed by polymerization.

[0013] When the cationic or amphoteric water-soluble polymer of the present invention is prepared by dispersion polymerization in salt water, it can be appropriately produced according to JP-A-62-20511, JP-A-10-212320, JP-A-2004-231822, etc. That is, the polymer is produced by dispersion polymerizing a mixture of a cationic monomer and / or anionic monomer and a nonionic monomer in a salt water solution in the presence of a polymer dispersant soluble in the salt water solution.

[0014] In the present invention, the cationic or amphoteric water-soluble polymer may contain a crosslinkable monomer such as N,N'-methylenebis(meth)acrylamide or triallylamine as a structural modifier during or after polymerization. When a crosslinkable monomer is used, it is present in a range of 200 ppm or less by mass based on the total amount of monomers. In addition, it is also effective to use a chain transfer agent such as sodium formate, isopropyl alcohol, or sodium methallyl sulfonate in combination as a method for adjusting crosslinkability. The addition rate is 0.001 to 1.0 mass% based on the total amount of monomers.

[0015] The cationic or amphoteric water-soluble polymer in the present invention needs a high molecular weight to obtain a high coagulation force. The molecular weight is expressed in terms of intrinsic viscosity, and the intrinsic viscosity of the water-soluble polymer in a 1N saline solution measured at 25°C is 15 to 30 dl / g, preferably 18 to 30 dl / g. If the intrinsic viscosity is lower than 15 dl / g, the effect of improving the retention and drainage and water squeezing is significantly reduced, and if it is higher than 30 dl / g, the quality of the paper, especially the formation, tends to be reduced, and the drainage and water squeezing also tends to be reduced, which is not preferable. The weight average molecular weight measured by the intrinsic viscosity method is preferably within the range of 10 to 30 million.

[0016] As the organic acid in the present invention, it is preferable to use a compound having a carboxy group, a sulfonic acid group, or a phenolic hydroxyl group. Two or more organic acids may be used. As the compound having a carboxy group, acetic acid, formic acid, propionic acid, oxalic acid, tartaric acid, citric acid, malic acid, lactic acid, adipic acid, sebacic acid, stearic acid, oleic acid, maleic acid, succinic acid, fumaric acid, gluconic acid, ascorbic acid, or salts thereof may be mentioned. Also, among organic acids having a carboxy group, polysaccharides or polysaccharide derivatives can be used, such as carboxymethyl cellulose, carboxyethyl cellulose, carboxymethylated starch or salts thereof, starch, methyl cellulose, ethyl cellulose, guar gum, trant gum, xanthan gum, sodium alginate, carrageenan, gum arabic, gelatin, and casein. Examples of those having a sulfonic acid group include styrenesulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid, 2-hydroxy-3-allyloxy-1-propanesulfonic acid, isoprene sulfonic acid, alkylbenzenesulfonic acid, and salts thereof. Examples of substances having a phenolic hydroxyl group include lignin, lignosulfonic acid, humic acid, nitrohumic acid, tannic acid, catechin, gallic acid, and salts thereof. Among these organic acids, those having a plurality of the same or different groups selected from carboxyl groups, sulfonic acid groups, and phenolic hydroxyl groups are preferred. In particular, citric acid, carboxymethyl cellulose, carboxyethyl cellulose, guar gum, xanthan gum, sodium alginate, carrageenan, humic acid, nitrohumic acid, tannic acid, catechin, gallic acid, or salts thereof are preferred because they provide effective effects. The anion equivalent value of the organic acid is preferably 0.1 meq / g or more (solid content).

[0017] In the present invention, organic acids having a certain molecular weight tend to be highly effective. In the present invention, the viscosity of a 0.2% by mass aqueous solution is used as an index of molecular weight, and a 0.2% by mass aqueous solution in the range of 5 to 300 mPa·s is effective, with 10 to 300 mPa·s being preferred. If it is lower than 5 mPa·s, the effect of improving the yield and drainage is low, and if it exceeds 300 mPa·s, dispersibility tends to be poor. The viscosity of a 0.2% by mass aqueous solution is a value measured using a Brookfield viscometer with a No. 1 rotor at 30 rpm. As the Brookfield viscometer, a TVB-10M manufactured by Toki Sangyo or the like is used.

[0018] These organic acids may be modified with a cationizing agent, an anionizing agent, or a crosslinking agent. Examples of the cationizing agent include glycidyltrialkylammonium halides such as glycidyltrimethylammonium chloride and 3-chloro-2-hydroxypropyltrimethylammonium chloride, or halohydrin compounds thereof. Examples of the anionizing agent include carboxylic acids having multiple carboxyl groups or anhydrides thereof, or salts thereof, oxoacids containing a phosphorus atom or salts thereof, ozone, and 2,2,6,6-tetramethylpiperidinooxy radical. Examples of crosslinking agents include N,N'-methylenebis(meth)acrylamide, triallylamine, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, 1,3-butylene glycol dimethacrylate, polyethylene glycol di(meth)acrylate, N-vinyl(meth)acrylamide, N-methylallylacrylamide, glycidyl acrylate, polyethylene glycol diglycidyl ether, acrolein, glyoxal, and vinyltrimethoxysilane.

[0019] In the present invention, after the cationic or amphoteric water-soluble polymer is added as the first liquid, an organic acid is added as the second liquid.

[0020] The cationic or amphoteric water-soluble polymer and organic acid of the present invention are added to the papermaking raw material before papermaking. Usually, in the papermaking process, the papermaking raw material transferred from the upstream with a pulp dry solids concentration of 2.0% by mass or more is diluted with white water or fresh water to a papermaking raw material with a pulp dry solids concentration of less than 2.0% by mass just before the papermaking machine. The diluted raw material is sprayed from a device called an inlet or head box into the papermaking machine and paper is made. Generally, it is diluted to 0.5 to 1.5% by mass, and these are called inlet raw material or head box raw material. A retention and drainage improver is added to these raw materials (hereinafter referred to as inlet raw material) and paper is made. The retention and drainage improvement system of the present invention is also applied to the inlet raw material.

[0021] The location of addition of the cationic or amphoteric water-soluble polymer and the organic acid in the papermaking process in the present invention is before or after a fan pump or before or after a screen, which is a shearing process. As long as the organic acid is added after the cationic or amphoteric water-soluble polymer in the present invention, any of these addition locations can be applied. In the present invention, since the cationic or amphoteric water-soluble polymer in the first liquid has a high reactivity with the organic acid in the second liquid, the effect can be achieved without going through a shearing process. That is, it is possible to add the first and second liquids after the papermaking raw material has passed through the fan pump and before the screen, or to add the first and second liquids after the papermaking raw material has passed through the screen. It is preferable to add the organic acid in the second liquid at the screen outlet after the papermaking raw material has passed through the screen.

[0022] The cationic or amphoteric water-soluble polymer in the present invention has a certain high molecular weight. The cationic groups in the cationic or amphoteric water-soluble polymer coagulate to form coarse flocs due to neutralization and cross-linking adsorption between the cationic groups in the cationic or amphoteric water-soluble polymer and the anionic cellulose fibers and fillers in the papermaking raw materials. The formed flocs are then gradually broken down into smaller flocs during transportation and shearing. If a substance in the second liquid is added as a system for improving retention and drainage, and shearing and mixing are insufficient, the diffusion of the formed flocs is slow and it takes time to form the flocs, resulting in the formation of coarse flocs, which result in the loss of fine fibers and fillers and the introduction of moisture into the flocs, resulting in a decrease in retention, drainage, and squeezing. The larger the molecular weight of the cationic or amphoteric water-soluble polymer in the first liquid, the more pronounced this phenomenon is. However, in the present invention, even under conditions of insufficient shearing or mixing, the organic acid added to the second liquid forms fine flocs through a reaction between the unreacted cationic groups in the polymers in the flocs and the cationic substances in the suspension of the papermaking raw material and the anionic organic acid, and the flocs are made into paper in the wire part. As a result, it is believed that the mechanism is such that the yield can be maintained or improved and the drainage and dewatering can be improved without introducing much moisture into the flocs. The papermaking method of the present invention is particularly effective when the shear force on the papermaking raw materials is weak or when the time from the addition of the organic acid to the arrival at the inlet is short. For example, in order to maximize the retention and drainage effect when the retention and drainage improver is mixed with the papermaking raw materials, it usually takes about 10 seconds for the retention and drainage improver to reach the inlet (head box) after the addition of the retention and drainage improver, but the organic acid of the present invention has high diffusibility into the papermaking raw materials and is effective even when the time to reach the inlet is within 5 seconds.

[0023] The types of paper to which the papermaking method of the present invention is applied include newsprint, wood-free printing paper, medium-quality printing paper, gravure printing paper, PPC paper, coated base paper, lightly coated paper, packaging paper, liner and core base paper board, etc. The organic acid of the present invention is effective for papermaking raw materials with a relatively low anion amount, i.e., cation demand. Specifically, if the cation demand is 0.03 meq / L or less, the organic acid of the present invention is effective. It is also effective even if the papermaking raw materials show cationicity (=anion demand). It is effective when applied to a papermaking system with a high addition rate of cationic or amphoteric starch, paper strength agents such as synthetic paper strength agents, or aluminum sulfate. The cation demand is expressed as a value (meq / L) measured by a commercially available particle charge meter (such as PCD-05 model manufactured by BTG) for the filtrate from Whatman No. 41 filter paper.

[0024] The cationic or amphoteric water-soluble polymer in the present invention is used by diluting and dissolving in water to 0.01 to 1.0% by mass, and the organic acid is used by diluting and dissolving in water to 0.01 to 10% by mass. The water used for dissolution can be distilled water, ion-exchanged water, tap water, industrial water, etc. These may be mixed. The diluted solution may be further diluted a second time or a third time. The addition rate of the cationic or amphoteric water-soluble polymer is in the range of 10 to 1000 ppm (pure polymer content) relative to the solid content of the stock. The addition rate of the organic acid is in the range of 10 to 5000 ppm (solid content) relative to the solid content of the stock.

[0025] The cationic or amphoteric water-soluble polymer and organic acid of the present invention can be used in combination with paper strength agents, sizing agents, and other papermaking chemicals. In addition, they may be used in combination with other retention and drainage improvers, but it is preferable to use only the retention and drainage improver system of the present invention, as this is more advantageous. EXAMPLES

[0026] The papermaking method of the present invention using a cationic or amphoteric water-soluble polymer and an organic acid will be specifically described below, but the present invention is not limited to the following examples.

[0027] (PAM-based water-soluble polymer sample) Cationic water-soluble polymer samples A and B according to the present invention, and anionic water-soluble polymer samples C and D outside the scope of the present invention were prepared by the usual methods of water-in-oil emulsion polymerization and dispersion polymerization in salt water. Their compositions and physical properties are shown in Table 1.

[0028] (Table 1) TIFF2025009112000003.tif2690 Monomer; DMQ: acryloyloxyethyltrimethylammonium chloride, AAM: acrylamide, AAC: acrylic acid Product form: E: Water-in-oil emulsion, D: Dispersion polymer in salt water Intrinsic viscosity: The intrinsic viscosity of a water-soluble polymer in a 1N saline solution measured at 25°C.

[0029] (Organic acid sample) Commercially available organic acid samples 1 to 8 according to the present invention were prepared. Their physical properties are shown in Table 2.

[0030] (Table 2) TIFF2025009112000004.tif52910.2 mass% aqueous solution viscosity; Viscosity of a 0.2 mass% aqueous solution of organic acid measured at 25°C.

[0031] Example 1 (Drainage performance evaluation test) Drainage performance was evaluated using a dynamic drainage analyzer (DDA, PulpEye). The cardboard was disintegrated, and the stock was adjusted to a beating degree of 270 mL. The stock was then diluted with fresh water to a stock solids content of 1% by mass, and the pH was adjusted before use as the inlet stock. The physical properties of the prepared inlet paper stock were pH 7.3, electrical conductivity 84.1 mS / m, SZP of the prepared inlet paper stock -8.0 mV, turbidity of the Whatman No. 41 filter paper filtrate 35 NTU (using HACH 2100P type), and cation demand 0.028 meq / L (using BTG PCD-05 type). A given amount of the prepared inlet stock was put into a DDA mixing tank with a wire at the bottom. After stirring for 5 seconds at 600 rpm, 0.5% by mass of commercially available cationic starch was added (relative to the stock solids), stirring for 40 seconds at 600 rpm, stirring for 5 seconds at 200 rpm, 0.1% by mass aqueous solution of sample A in Table 1 was added as the first liquid at 240 ppm (pure polymer content) relative to the stock solids, stirring for 3 seconds at 200 rpm (assuming addition to the screen inlet), sample 1 in Table 2 was added as the second liquid at 500 ppm (solid content), stirring for 4 seconds at 200 rpm (assuming addition to the screen outlet), and the stock was sucked under a reduced pressure of 300 mBar, and the drainage time and sheet moisture content were measured when a sheet was formed on the wire. Similar tests were also conducted by changing the combination or addition rate of the first liquid sample in Table 1 and the second liquid sample in Table 2. These results are shown in Table 3.

[0032] Comparative Example 1 Using the same prepared inlet paper stock as in Example 1, similar tests were carried out under similar conditions using the cationic water-soluble polymer sample, the anionic water-soluble polymer sample, and the commercially available bentonite in Table 1. The results are shown in Table 3.

[0033] (Table 3) TIFF2025009112000005.tif6791

[0034] In the examples in which an organic acid sample was added after the cationic water-soluble polymer sample of the present invention was added, the drainage time was shortened and the sheet moisture content was lower than in the comparative examples. In the comparative examples in which the addition method was outside the scope of the present invention, no results were obtained showing both a shortened drainage time and a lower sheet moisture content. It was confirmed that the drainage performance and water squeezing performance of the papermaking method of the present invention are excellent.

[0035] Example 2 (Drainage performance evaluation test) Drainage performance was evaluated using a dynamic drainage analyzer (DDA, PulpEye). Inlet paper stock prepared for fine papermaking was used for the test. The physical properties of the prepared inlet paper stock were pH 7.9, electrical conductivity 34.1 mS / m, SZP of the prepared inlet paper stock was 17.8 mV, the turbidity of the Whatman No. 41 filter paper filtrate was 125 NTU (using HACH 2100P type), and the cation demand was 0.009 meq / L (using BTG PCD-05 type). A predetermined amount of the prepared inlet stock was put into a DDA mixing tank with a wire at the bottom. After stirring for 5 seconds at 600 rpm, 1% by mass of aluminum sulfate was added, after stirring for 20 seconds at 600 rpm, 1% by mass of commercially available cationized starch was added (relative to the stock solids), after stirring for 20 seconds at 600 rpm, after stirring for 5 seconds at 200 rpm, 100 ppm (pure polymer content) of a 0.1% by mass aqueous solution of sample A in Table 1 was added to the stock solids as the first liquid (as a first liquid), after stirring for 20 seconds at 200 rpm (assuming addition to the screen inlet), after stirring for 20 seconds at 200 rpm (assuming addition to the screen outlet), after stirring for 10 seconds at 200 rpm (assuming addition to the screen outlet), the stock was sucked under a reduced pressure of 250 mBar, and the drainage time and sheet moisture content were measured when a sheet was formed on the wire. The dried sheet was placed in a crucible and incinerated at 525°C for 2 hours, and the ash content in the paper was calculated. Similar tests were also conducted by changing the combination or addition rate of the first liquid sample in Table 1 and the second liquid sample in Table 2. The results are shown in Table 4.

[0036] Comparative Example 2 Using the same prepared inlet paper stock as in Example 2, similar tests were carried out under similar conditions using the cationic water-soluble polymer sample, the anionic water-soluble polymer sample, and the commercially available colloidal silica in Table 1. The results are shown in Table 4.

[0037] (Table 4) TIFF2025009112000006.tif3691

[0038] In the comparative example where the second liquid was used with an increased addition rate of a PAM-based anionic water-soluble polymer, excessive moisture was brought into the formed floc, resulting in a high sheet moisture content. When the amount was further increased, the sheet moisture content became even higher, and the water drainage tended to become poor. When the organic acid of the present invention was used with an increased addition rate, the sheet moisture content decreased.

[0039] Example 3 (Drainage performance evaluation test) Drainage performance was evaluated using a dynamic drainage analyzer (DDA, PulpEye). The cardboard was disintegrated, and the stock was adjusted to a beating degree of 270 mL. The stock was then diluted with fresh water to a stock solids content of 1% by mass, and the pH was adjusted before use as the inlet stock. The physical properties of the prepared inlet paper stock were pH 7.4, electrical conductivity 252 mS / m, SZP of the prepared inlet paper stock -4.7 mV, turbidity of the Whatman No. 41 filter paper filtrate 66 NTU (using HACH 2100P type), and cation demand 0.123 meq / L (using BTG PCD-05 type). A predetermined amount of the prepared inlet stock was put into a DDA mixing tank with a wire at the bottom. After stirring for 5 seconds at 450 rpm, 0.5% by mass of commercially available cationic starch was added (relative to the stock solids), stirring for 40 seconds at 450 rpm, stirring for 5 seconds at 150 rpm, 0.1% by mass aqueous solution of sample A in Table 1 was added to the stock solids at 250 ppm (pure polymer content) as the first liquid, stirring for 4 seconds at 150 rpm (assuming addition to the screen inlet), sample 3 in Table 2 was added at 500 ppm (solids content) as the second liquid, stirring for 4 seconds at 150 rpm (assuming addition to the screen outlet), and the stock was sucked under a reduced pressure of 300 mBar, and the drainage time and sheet moisture content were measured when a sheet was formed on the wire. Similar tests were also conducted by changing the combination of the first liquid sample in Table 1 and the second liquid sample in Table 2. These results are shown in Table 5.

[0040] Comparative Example 3 Using the same prepared inlet paper stock as in Example 3, similar tests were carried out under similar conditions using the cationic water-soluble polymer sample, the anionic water-soluble polymer sample, and the commercially available bentonite in Table 1. The results are shown in Table 5.

[0041] (Table 5) TIFF2025009112000007.tif3591

[0042] When the organic acid of the present invention was used and the addition rate was increased, the drainage time was shorter than in the comparative example, and the sheet moisture content was reduced. When the PAM-based anionic water-soluble polymer sample C was used in the second liquid, the sheet moisture content tended to be even higher, and it was not possible to increase the addition rate.

[0043] Example 4 (Yield rate measurement test) A retention rate measurement test was carried out using a dynamic drainage analyzer (DDA, PulpEye). A predetermined amount of the inlet stock prepared in the same manner as in Example 3 was put into a DDA mixing tank with a wire at the bottom. After stirring for 5 seconds at 450 rpm, 0.5% by mass of cationic starch was added (relative to the stock solids), stirring for 40 seconds at 450 rpm, stirring for 5 seconds at 150 rpm, and then a 0.1% by mass aqueous solution of Sample A in Table 1 was added as the first liquid at 250 ppm (pure polymer content) relative to the stock solids, stirring for 4 seconds at 150 rpm (assuming addition at the screen inlet), and Sample 3 in Table 2 was added as the second liquid at 500 ppm (solid content) relative to the stock solids, stirring for 4 seconds at 150 rpm (assuming addition at the screen outlet), and the stock was sucked under a reduced pressure of 300 mBar, and the filtrate at the time when a sheet was formed on the wire was collected and filtered with ADVANTEC No. 2 filter paper, and the SS was measured to determine the total retention rate. Similar tests were also carried out by changing the combination or addition rate of the first liquid sample in Table 1 and the second liquid sample in Table 2. The results are shown in Table 6.

[0044] Comparative Example 4 Using the same prepared inlet paper stock as in Example 4, the same tests were carried out under the same conditions as in Example 4 using the cationic water-soluble polymer sample, the anionic water-soluble polymer sample, and the commercially available bentonite in Table 1. The results are shown in Table 6.

[0045] (Table 6) TIFF2025009112000008.tif3691

[0046] It was found that the papermaking method of the present invention can maintain or improve the retention rate and improve the drainage and water squeezing properties compared to the comparative example.

Claims

1. A papermaking method comprising adding a cationic or amphoteric water-soluble polymer having as its constituent units 5 to 100 mol % of a cationic monomer represented by the following general formula (1), 0 to 30 mol % of an anionic monomer represented by the following general formula (2), and 0 to 95 mol % of a nonionic monomer to a papermaking raw material before papermaking in a papermaking process, and then adding an organic acid. General formula (1) R 1 is hydrogen or a methyl group, R 2 , R 3 is an alkyl or alkoxy group having 1 to 3 carbon atoms, R 4 represents an alkyl or alkoxy group having 1 to 3 carbon atoms, an alkyl group having 7 to 20 carbon atoms, or an aryl group; A represents oxygen or NH; B represents an alkylene group having 2 to 4 carbon atoms; X 1 - represents an anion. General formula (2) R 5 is hydrogen, a methyl group or a carboxymethyl group, and Q is SO 3 - , C 6 H 4 SO 3 - , CONHC (CH 3 ) 2 CH 2 SO 3 - , C 6 H 4 COO - Or COO - , R 6 is hydrogen or COOY 2 , Y 1 Or Y 2 represents a hydrogen or a cation, respectively.

2. 2. The papermaking method according to claim 1, wherein the organic acid has a plurality of the same or different groups selected from the group consisting of a carboxy group, a sulfonic acid group, and a phenolic hydroxyl group.

3. The papermaking method according to claim 1 or 2, characterized in that the organic acid has a 0.2 mass % aqueous solution viscosity (25° C.) in the range of 5 to 300 mPa·s.

4. 3. The papermaking method according to claim 1, wherein the cationic or amphoteric water-soluble polymer has an intrinsic viscosity in a 1 N saline solution measured at 25° C. of 15 to 30 dl / g.

5. 3. The papermaking method according to claim 1, wherein the organic acid is added at a screen outlet in the papermaking process.